History and characterization of atmospheric black carbon in the Anthropocene - Ellis, Aja Anne (Curtin University, 2017)
Black carbon aerosols (BC) from incomplete combustion have substantial effects on the atmosphere and climate, but climate forecasting is poorly constrained due to uncertainties in atmospheric lifetime and removal rates. Herein, we detail the recent history, characteristics, and composition of BC deposited in rain from Australia and ice cores from Antarctica. Results show new complex particle characteristics and an increase in BC in West Antarctica driven by changing emissions and atmospheric transport conditions.